Three waves of hate speech spreading faster than the pandemic in Malaysia: an analyses of outgroup populist narratives and hate speech during the COVID-19 - Kevin Fernandez, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Societal responses in disquietude circumstances during the corona virus (COVID-19) has been diverse, choosing to express themselves by engaging in online hate speech depending on the locality and pre-existing state of affairs of individual nation states. This exercise argues that there were three waves of hate speech in Malaysia during the COVID-19 pandemic. The first was a nationalistic form narrative targeting the mainland Chinese. The second one was in the form of defending the ummah because the Tabligh cluster was a large gathering which caused a significant number of infections during the initial stages of the pandemic. The last one was against the global ummah, defending the sovereign state and other Malaysians from being infected by foreign and migrant workers, especially the Rohingya refugees. We argue that they are all not in contradictory of each other, but in actual fact, glued by populist narratives of local leaders. The relativist approach, using the qualitative content analysis method was adopted to better understand the underlying factors which led to these manifestations of hate captured online and sometimes its spillover effects expressed in real life. This study concludes that there is an abstract corelation between populist exclusionary statements by political leaders and the responding hate speech sentiments being shared online during the pandemic.